PEMBERDAYAAN NELAYAN MELALUI PENGOLAHAN IKAN PASCA PRODUKSI - Pratomo, Heru (Universitas Negeri Yogyakarta, 2003)
The activities of this technology application purpos : (1) gives skills in fish processing to the wife of fisherman in Trisik Beach.Desa Banaran, Kecamatan Galur, Kabupaten Kulon Progo, especially to make bandengfish presto, fish meatballs, fish noodles, fish shredded, and fish ketchup; (2) increase the fisherman income by means of fish processing.These activities are followed by 14 women, and carried out in three days in Trisik. The methods of this activity are talkactive and practice in fish processing. The topics of the talk cti e are: (1) The contents of nutrient in fish, (2) Fish processing technology, (3) The health technology in food processing, (4) The sanitation of area manufacture, (5) Analysis in exertion fish processing, and (6) The methods of packing production and getting sertificate from Health Department. The topics in practice of fish processing are making bandeng fish presto, fish meatballs, fish noodles, fish shredded, and fish ketchup. ,The 'results 6f'these activities indicate that the participants are very interest. The participants are interesting in the processing of bandeng fish presto, fish meatballs, and fish noodles. The conclucions of these activities are: (I) the activities have succeeded agree with the purpose, and (2) the participants have had skills in fish processing, especially in making bandengfish presto, fish meatballs, fish noodles, fish shredded, and fish ketchup.Key words: fish processing, and increase of fisherman income